PENGUASAAN LEKSIKON ARKAIS BAHASA MELAYU AMBON DI KALANGAN PEMUDA DI KOTA AMBON - Erniati erniati (Gramatika: Jurnal Ilmiah Kebahasaan dan Kesastraan, 2019)
The condition of the regional languages ​​in Maluku is currently diminishing in speakers. This happened because of the causative relationship with the attitudes and choices of speakers about the language and the existence of Ambonese Malay. Ambon Malay Language is the language of instruction in interethnic informal communication in Maluku. Ambon Malay language as a factor formed by a long process of assimilation over a long period of time is undeniably absorbing most of the vocabulary from Portuguese, Dutch, and local languages. In its development, various external factors such as language attitudes, language interests, preferences, and inheritance of language registers in various levels were alleged to have caused a kind of 'archaism' or 'aging' process towards certain vocabulary, especially vocabulary originating from or influenced by European languages and regional languages. When the need to convey meaning in lexicons, phrases, and sentences in one language is not proportional to the mastery of the existing vocabulary, speakers tend to replace these elements with lexicons and phrases from languages ​​that are at a lower level or variety / informal. In the end, the use of lexicons and vocabulary from regional languages ​​or old languages ​​slowly began to be replaced by elements from more modern languages, or which occupy normative functions in communication by users of that language. This study is a type of experimental research using a quantitative approach. The purpose of this study is expected to be able to measure the mastery of archaic lexicons in the youth age group, namely in the microlinguistic level and identify mastery of archaic lexicons at the syntactic, semantic morphological level. The results showed that the mastery of the archaic lexicon in the two villages was in the poor category.